Using geospatial techniques to detect land cover changes in Baqubah district, Diyala, Iraq. - Ahmed B. Khalaf; Suha A. Hitler; Shyma T. Faleh (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
This study was conducted on the land covers spread in Baquba district, Diyala Governorate, central Iraq, northeast of Baghdad, between longitudes 44° 25 '04.508"- 44°58' 05.640" and latitudes 33° 24' 34.667 "- 33° 52' 16. 444 "    with an area of 1820.941 km2. In order to study the changes in land cover, we relied on the field survey to determine ground control points we also used data from two US satellites, Landsat 8, for the years 2016 and 2023, as the supervised classification process was carried out on the satellite data, and the classification result showed that we obtained 3 categories: vegetation cover, water and others (buildings, streets, barren lands, etc.). They were identified and compared with the ground control points, which numbered 120 points. The classification accuracy of the satellite data was calculated using the Kappa statistical measure to calculate the accuracy and was 0.86 and 0.88 for the years 2016 and 2023, respectively. The spectral indicators NDVI, NDWI were also used. The results of the study indicate a decline in vegetation cover and water resources with an area (324,859 km2 and 50,364 km2, respectively), compared to an increase in urban areas by an area of 375.224 km2, which requires taking appropriate measures to achieve sustainable development.